Extraction of proteinaceous components and biominerals from cold water fish fileting side streams: a review - Kendler, Sophie; Sasidharan, Abhilash; Rustad, Turid (Frontiers in Sustainable Food Systems, 2024)
Fileting is a popular form of processing methods and in addition to being sold fresh or frozen, filets are used for preparation products battered and breaded filets. This generates considerable amount of side streams like skin, frames, and cut-offs which forms around 30–70% of the total body weight. The European Waste Framework Directive 2008 and recent amendments [EU WFD (2018/851)] stipulates comprehensive regulations which the manufacturers must follow while handling the side streams generated during the processing. This demands a detailed compilation of information regarding the yield, classification and valorization potential of side streams associated with the fileting operations of the cold-water finfishes. The side streams are a rich source of proteins including structural proteins like collagen and biominerals such as hydroxyapatite which find multiple application in food and pharmaceutical industry. Previously, the recovery of these components was performed by extensive chemical treatment with acids or bases, including subsequent washing steps. Nowadays, green extraction methods, defined as technologies with reduced energy and chemical consumption, should be considered to achieve a green shift in the food industry. Nevertheless, industrial upscaling of green extraction methods and subsequent refinement of the isolated compounds must be further evaluated and improved in order to achieve a green shift in food industry by using side-stream derived compounds as ingredients. Moreover, legislations as well as national and international regulations must be considered and evaluated. Even though a number of articles are recently available regarding seafood side stream valorization, this review focus on side streams generated predominantly from cold water fish species and also discusses sustainable green technologies to be included during the recovery process.